Utilization of infrared radiation to human health - Rianti, Emillia Devi Dwi (Universitas Wijaya Kusuma Surabaya, 2013)
Infrared radiation is an electromagnetic wave, which has a wavelength between 700 nm and 1 mm. Electromagnetic wave itself has a definition, is a wave that can propagate even if there is no medium. Infrared light has a longer wavelength than visible light, but shorter than radio waves radiation. It is known that the red (from the Latin infra,